Synonymy of some Cicadellidae (Hemiptera: Auchenorrhyncha) known from Tuva Republic of Russia - Emeljanov, Alexandr F.; Saryglar, Syldys H. (Zootaxa, 2017)
Five new species-level synonyms are established in the subfamily Deltocephalinae for the genera Achaetica Emeljanov, 1959, Mocuellus Ribaut, 1946, and Calamotettix Emeljanov, 1959. Chloriona jegoroviensis Vilbaste, 1980 is treated as a nomen nudum.